Send back the money the Free Church of Scotland and American slavery - Whyte, Iain. (Cambridge : James Clarke & Co Ltd, 2012)
Iain Whyte investigates the history of slavery and its abolition with a particular assessment of Scotland's role in emancipation.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Free Church of Scotland -- Political activity -- History; Free Church of Scotland; Free Church of Scotland; Antislavery movements -- United States -- History; Antislavery movements -- Scotland -- History; SOCIAL SCIENCE -- Slavery; Antislavery movements; Political participation; Scotland; United States; RELIGION / Christian Church / History; Electronic books; History